PENGARUH BERBAGAI LEVEL IRIGASI BAWAH PERMUKAAN DAN APLIKASI BIOCHAR TERHADAP PERTUMBUHAN DAN HASIL PADI SAWAH - GUSTI AGUNG KADE ERNA WARDANA; NINI MILA RAHNI; I MADE WIDANA ARSANA; LAODE SABARUDDIN; MIRZA ARSIATY ARSYAD; ARSY AYSYAH ANAS (Jurnal Agroteknos, 2023)
This research aims to determine the effect of subsurface irrigation water level and biochar application on the growth and yield of lowland rice. The research was conducted at Experimental Garden I, Faculty of Agriculture University Halu Oleo. The study consisted of two factors of treatments laid out in an RBCD-based factorial experimental design. The first factor consisted of four levels of subsurface irrigation (S) (i.e., 0, 4, 8, and 12 cm below the soil surface). The other factor also consisted of four levels of rice husk biochar (B) (i.e., 0, 10, 20, and 30 metric tons ha–1). Each treatment combination was given three replications. The collected data were analyzed with ANOVA and the differences among treatments were tested with DMRT at P=0.05. The study showed that both factors had no interaction effect on all parameters. The subsurface irrigation treatments, however, showed significant effects on plant height (56, 70, 84 DAS), leaf area (56, 70 DAS), flag leaf area, dry weight of root and shoot, panicle length, number of grains per panicle, grain weight after harvest per hill, dry weight of 1,000 rice grains, and yield. On the other hand, the biochar treatment only showed significant effects on leaf area at 70 DAS, flag leaf area, number of grains per panicle, grain weight after harvest per hill, and dry weight of 1,000 rice grains.